PTU-271 Hidden morbidity following colorectal resection: postoperative evaluation. (22nd June 2015) - Thorpe, GC; Hernon, J
Abstract : Introduction: The implementation and evaluation of Enhanced Recovery after Surgery programmes over the past 15 years has ensured the accurate reporting of inpatient morbidity post colorectal resection. However, there is a paucity of audit or research examining post-operative morbidity in the early discharge period. Method: 142 consecutive patients undergoing elective (n = 98) or emergency (n = 44) colorectal resection over a three-month period were invited to attend a nurse-led outpatient clinic at 30 days post-discharge. Audit data were collected at two time-points, discharge from hospital and at clinic. Audit templates were developed using the Postoperative Morbidity Survey, 1 Clavien-Dindo classification criteria 2 and modified to include additional colorectal surgery-specific outcomes. Results were recorded and analysed using SPSS. Results: Unanticipated findings relating to post-discharge morbidity identified through the audit included: 35% (n = 32) of infection-free inpatients developed surgical site infections following discharge. 34% (n = 47) of all patients had significant urinary symptoms when seen in clinic. Dietary implications at 30 days post-discharge included an appetite of half or less than usual intake in 27% of patients (n = 37) and moderate to major changes in dietary intake compared to their pre-operative diet in 30% (n = 42). 27% (n = 38) of patients had an ileostomy; of those without an ileostomy, 20% (n = 21) had four or more daily bowel movements, with 22% (n = 23) describing their stool consistency as watery, loose or unsettled. 45% (n = 46) of those without an ileostomy reported one or more problematic bowel symptom related to their surgical experience at 30 days post-discharge. Conclusion: These audit findings suggest that individuals undergoing colorectal resection experience significant levels of post-discharge morbidity, extending the burden on them and the services required to support them for longer than may have been previously anticipated. Nurse-led follow-up using auditable documentation templates facilitates the recognition and reporting of complications following discharge and provides valuable support for patients. Disclosure of interest: None Declared. References: Grocott MPW, et al . The Postoperative Morbidity Survey was validated and used to describe morbidity after pelvic surgery. J Clin Epidemiol 2007;60:919–928 Dindo D, et al . Classification of Surgical Complications: a new proposal with evaluation in a cohort of 6336 patients and results of a survey. Ann Surg. 2004;240(2):205–213